Wear behavior of A356\M7C3 and A356\SiC particulate metal-matrix composites - Yilmaz, Osman; Buytoz, Soner (My University, 2002)
The stability of M7C3 carbides as reinforcement for A356 materials for tribological applications has been investigated. For this purpose, A356\M7C3, A356\SiC and A356/M7C 3/SiC composites were prepared by powder metallurgy and tested at room temperature against SAE 4620 steel ring and AISI 304 stainless steel counterfaces under the load of 50 N. Tribological behavior was evaluated by weight loss measurements of specimens and counterfaces. The wear behavior of A356/M7C3 composite gave an excellent result as function of the applied load, because M7C3 particles acts as load bearing elements due to their excellent bonding to the Al matrix, and their interfaces withstanded the wear stresses even at the highest applied load.
Proceedings of the 3rd International Powder Metallurgy Conference -- 4 September 2002 through 8 September 2002 -- Ankara -- 62829
Keywords: Al based Metal Matrix Composites; Powder Metallurgy